MONDO: a neutron tracker for particle therapy secondary emission characterisation. (28th March 2017) - Marafini, M; Gasparini, L; Mirabelli, R; Pinci, D; Patera, V; Sciubba, A; Spiriti, E; Stoppa, D; Traini, G; Sarti, A
Abstract: Tumour control is performed in particle therapy using particles and ions, whose high irradiation precision enhances the effectiveness of the treatment, while sparing the healthy tissue surrounding the target volume. Dose range monitoring devices using photons and charged particles produced by the beam interacting with the patient's body have already been proposed, but no attempt has been made yet to exploit the detection of the abundant neutron component. Since neutrons can release a significant dose far away from the tumour region, precise measurements of their flux, production energy and angle distributions are eagerly sought in order to improve the treatment planning system (TPS) software. It will thus be possible to predict not only the normal tissue toxicity in the target region, but also the risk of late complications in the whole body. The aforementioned issues underline the importance of an experimental effort devoted to the precise characterisation of neutron production, aimed at the measurement of their abundance, emission point and production energy. The technical challenges posed by a neutron detector aimed at high detection efficiency and good backtracking precision are addressed within the MONDO (monitor for neutron dose in hadrontherapy) project, whose main goal is to develop a tracking detector that can target fast and ultrafast neutrons. A full reconstruction of two consecutive elastic scattering interactions undergone by the neutrons inside the detector material will be used to measure their energy and direction. The preliminary results of an MC simulation performed using the FLUKA software are presented here, together with the DSiPM (digital SiPM) readout implementation. New detector readout implementations specifically tailored to the MONDO tracker are also discussed, and the neutron detection efficiency attainable with the proposed neutron tracking strategy are reported.